(untitled) (Journal of Health, Population and Nutrition, 2013)
Reactive arthritis (ReA) is a spondyloarthropathic disorder characterized by inflammation of the joints and tissues occurring after gastrointestinal or genitourinary infections. Diagnostic criteria for ReA do not exist and, therefore, it is subject to clinical opinion resulting in cases with a wide range of symptoms and definitions. Using standardized diagnostic criteria, we conducted a systematic literature review to establish the global incidence of ReA for each of the three most commonly-associated enteric pathogens: Campylobacter, Salmonella, and Shigella. The weighted mean incidence of reactive arthritis was 9, 12, and 12 cases per 1,000 cases of Campylobacter, Salmonella and Shigella infections respectively. To our knowledge, this is the first systematic review of worldwide data that use well-defined criteria to characterize diarrhoea-associated ReA. This information will aid in determining the burden of disease and act as a planning tool for public-health programmes. DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16515 J HEALTH POPUL NUTR 2013 Sep; 31(3): 299-307